Development of earth leakage circuit breaker with an auto re-closer unit - Mohd Tarmizi, Rahim (2009)
Power system protection is the most important requirement before the power system is put into operation. Electrical energy has caused dangers both to the human and the machines. Protection system is mostly controlled by the Earth Leakage Circuit Breaker (ELCB). This device is the brain of the protection system that monitors input current from power line by it sensor Zero phase Current Transformer (ZCT), then sending the signals to the mechanical switch to tripped the circuit breaker. ELCB is widely applied by consumer weather it is for resident, factory, laboratory and also power distribution. Power system protection can be implemented at various stages and various types of protection devices. Because industrial operation requires protection of their Equipment from the lightning, short-circuit and also over-current, so the ELCB will serve the purpose as the protection of their system. This project will attempt to improve and design the currently ELCB by using PIC microcontroller so that it have the ability to identify the fault, act accordingly, display the fault and also to re-close it back to normal. The PIC micro controller will cause the ELCB to trip when there is unbalance current from power line flow through life line and neutral line is ≥100mA. In order to design it, first thing of the current from the power line need to be measure in order to monitor it using ZCT including testing the fault (over current, lightning and short circuit) and when such condition arise, it will isolate the load from power line in the shortest time possible without harming the any other electrical devices. In this project PIC microcontroller will be used to control and operate the SSR, thus replacing the current mechanical switch.